Epidemiological characteristics of acute respiratory viral infection and influenza in Russian Federation and Moscow - T. S. Saltykova; B. A. Zhigarlovsky; A. V. Ivanenko; N. A. Volkova; V. I. Antonova; N. I. Briko (Журнал инфектологии)
Аim: Give an epidemiological description of the incidence of acute respiratory viral infection and influenza in the Russian Federation and Moscow.Materials and methods: The form of the federal state statistical observation № 2 “Information on infectious and parasitic diseases” for 2007–2017. When analyzing the etiological structure of the agents of ARVI and influenza in Moscow, protocols were used for weekly laboratory tests of agents of ARVI and influenza conducted by the Center for Hygiene and Epidemiology in Moscow.Results: The epidemic process of ARVI in Russia is characterized by a stabilization of morbidity with an average annual growth rate of 0,4%, and Moscow has a moderate tendency to reduce morbidity with an average annual rate of decline of 2,3%. The highest incidence of ARVI is observed among children under 1 year, 1–2 years and 3–6 years. The greatest proportion in the structure of the incidence of ARVI is children under 17 years. Both for Russia and for Moscow, there is a pronounced tendency to reduce the incidence of influenza. In contrast to ARVI, the largest proportion of people with influenza in Russia and in Moscow are adults, but the highest incidence rates are registered among the children. The epidemic rise of the incidence of ARVI and influenza in Moscow starts 10–12 weeks earlier than in the Russia as a whole.Conclusion: For the epidemic of ARVI in Moscow and in Russia it is typical to involve children under 1 year, 1–2 years and 3–6 years. In Moscow in 2016 and 2017 there is a significant increase in the incidence of influenza among children under 1 year and 1–2 years. In contrast to the Russian Federation for Moscow among the causative agents of non-influenza etiology, dominated parainfluenza viruses (1–3 types) and adenoviruses.